Tattoos do not affect exercise-induced localised sweat rate or sodium concentration. Issue 11 (November 2019) - Rogers, Ethan; Irwin, Christopher; McCartney, Danielle; Cox, Gregory R.; Desbrow, Ben
Abstract: Objectives: Skin tattoos have been shown to reduce localised sweat rate and increase sweat sodium concentration ([Na + ]) when sweating is artificially stimulated. This study investigated whether similar responses are observed with exercise-induced sweating. Design: Unblinded, within-participant control, single trial. Methods: Twenty-two healthy individuals (25.1 ± 4.8 y (Mean ± SD), 14 males) with a unilateral tattoo ≥11.4 cm 2 in size, ≥2 months in age, and shaded ≥50% participated in this investigation. Participants undertook 20 min of intermittent cycling (4 × 5 min intervals) on a stationary ergometer in a controlled environment (24.6 ± 1.1 °C; 64 ± 6% RH). Resultant sweat was collected into absorbent patches applied at two pairs of contralateral skin sites (pair 1: Tattoo vs. Non-Tattoo; pair 2: Control 1 vs. Control 2 (both non-tattooed)), for determination of sweat rate and sweat [Na + ]. Paired samples t -tests were used to determine differences between contralateral sites. Results: Tattoo vs. Non-Tattoo: Neither sweat rate (Mean ± SD: 0.92 ± 0.37 vs. 0.94 ± 0.43 mg·cm −2 ·min −1, respectively; p  = 0.693) nor sweat [Na + ] (Median(IQR): 37(32–52) vs. 37(31–45) mM·L −1, respectively; p  = 0.827) differed. Control 1 vs. Control 2: Neither sweat rate (Mean±SD: 1.19 ± 0.53 vs. 1.19 ± 0.53 mg·cm −2 ·min −1, respectively; p  = 0.917) nor sweat [Na + ] (Median(IQR): 29(26–41) vs. 31(25–43) mM·L −1, respectively; p  = 0.147) differed. The non-significant differences for sweat rate and [Na + ] between Tattoo vs. Non-Tattoo were inside the range of the within participant variability (sweat rate CVi = 5.4%; sweat [Na + ] CVi = 4.4%). Conclusions: Skin tattoos do not appear to alter the rate or [Na + ] of exercise-induced sweating. The influence of skin tattoos on localised sweat responses may have previously been over-estimated.